Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1039/c4mb00164h
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology study on the mechanism of traditional Chinese medicine for upper respiratory tract infection

Abstract: Traditional Chinese medicine (TCM) is a multi-component and multi-target agent and could treat complex diseases in a holistic way, especially infection diseases. However, the underlying pharmacology remains unclear. Fortunately, network pharmacology by integrating system biology and polypharmacology provides a strategy to address this issue. In this work, Reduning Injection (RDN), a well-used TCM treatment in the clinic for upper respiratory tract infections (URTIs), was investigated to interpret the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 64 publications
0
43
0
Order By: Relevance
“…Since CA and SCO, IsoB and SCO (each structure was shown in Fig. 2) had the different skeletons, they could interact with different target proteins in the pathway of LPS induced PGE 2 release process, so that to produce synergism3940. But when the concentration reaches a certain level, the inhibition rate will not increase with the increasing of the concentration, so it became antagonism.…”
Section: Resultsmentioning
confidence: 99%
“…Since CA and SCO, IsoB and SCO (each structure was shown in Fig. 2) had the different skeletons, they could interact with different target proteins in the pathway of LPS induced PGE 2 release process, so that to produce synergism3940. But when the concentration reaches a certain level, the inhibition rate will not increase with the increasing of the concentration, so it became antagonism.…”
Section: Resultsmentioning
confidence: 99%
“…The underlying mechanism is normally not clear . It was reported that polyphenol compounds and iridoids were the main components in RDN, including Chlorogenic Acid, Caffeic Acid, Isochlorogenic Acid B, Isochlorogenic Acid A, Isochlorogenic Acid C,Geniposide and so on (Wang et al, 2014;Zhang et al, 2014). Recent studies demonstrated that Chlorogenic Acid, Isochlorogenic Acid A, Isochlorogenic Acid B and Isochlorogenic Acid C could attenuate the release of PGE 2 and IL-6 in macrophage Shan et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…A network pharmacology approach was employed to uncover the molecular mechanism of Chinese medical herbs by Zhang et al, 2014. It was revealed that RDN could regulate MAPK pathways via interacting MEK1, JNK, ERK, p38 proteins as well as some key enzymes (COX and iNOS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all these biomarkers are targeting to some specific disease, none of them can be used to elucidate the symptom or symptom combination. It has been demonstrated that in the context of TCM theory, network biology based approaches can prioritize disease-associated genes, predict the target profiles and pharmacological actions of herbal compounds, interpret the combinational rules and network regulation effects of herbal formulae545556, thus the biomarkers for our symptomatic indicators might be a network based profile instead of a single molecule. The identification of such a network based profile will rely on a larger scale study, which is now developed underway as further study of this two-staged trial.…”
Section: Discussionmentioning
confidence: 99%